Tillage, Mulching and Nitrogen Based Weeds in Wheat and its Impacts on Yield - Mahapatra, N; C Senapati, Kishore (International Journal of Psychosocial Rehabilitation, 2025)
In the production systems, weeds play an important role. They compete with water, nutrients, and air and light crops, resulting in poor cultivation. Many small leavened, large leavened and grassy weeds are associated with the wheat and ultimately reduce the yield of grain. In many regions of South Asia, weeds are the main restrictions on wheat production. More than 90 weed species infecting this crop in the Indian Subcontinent are estimated to be 20-40% dependent on weed species, and the direct yield loss caused by mixed weed flora. In Nepal, weeds can reduce the wheat yield by as much as 50 percent, depending on the severity and species of weeds, sometimes even higher. Several studies have shown that stroke mulch reduces the amount of grassy and broad blade weeds to 80% in wheat. Tillage is a significant factor in weed management program. Surface seed technology or zero tillage is becoming more popular in wheat production as the occurrence of the most troublesome weeds Chenopodium album L. and Phalaris minor Retz has decreased. Soil condition has improved due to decomposition of crop residues, infiltration rate increases, reduced preparation cost and pre-sowing of the rice-wheat process in wheat. The use of the lower dose of nitrogen is shown to be minimal weed dry and increased significantly with the higher nitrogen level.